HUBUNGAN ANTARA NOMOR FERIT DENGAN LAJU KOROSI PADA BAJA TAHAN KARAT AUSTENITIK DALAM KONDISI AS CAST DAN AS WELD - Huda, Saiful (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2004)
Austenitic stainless steel has superior characteristic in corrosion resistance, but it tends to crack when welded. To prevent the crack during the welding, Cr equivalent can be increased to produce fasa ferit in austenitic metric. Austenitic stainless steel containing minimum 4% of ferit will avoid weld cracking; however, it will decrease the corrosion resistance. The aim of this research is to know the corrosion rate of austenitic stainless steel with different ferit content in the as cast and as weld conditions. The different content of ferit is obtained in two ways. First, in as cast condition it is obtained by choosing 3 different materials with different chemical compound. Cr equivalent and Ni equivalent are calculated so that by using Schaeffer diagram the ferit content in the main metal ( austenitic steel) can be identified that is ferit number 7, 9, and 10.The second way is obtained through the welding process using different electrode for different main metal. By taking 20% of the delusion, austenitic stainless steel containing ferit number 6,8,and 9 is obtained. Corrosion rate, tensile strength, and impact tests are done on these six materials. The findings show that in the same ferit number, as weld stainless steel is more corrosive and the impact strength is much lower than that of as cast. Meanwhile, in the same material(as weld as well as as cast) the bigger the ferit number the more the corrosion and the lower the tensile strength and the impact are.